2008
DOI: 10.1248/yakushi.128.1293
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin Isolated from <i>Erigeron multiradiatus</i> Inhibits High Glucose-mediated Vascular Inflammation

Abstract: Erigeron multiradiatus (Lindl.) Benth is a traditional Tibetan medicine herb long used to treat various diseases related to in‰ammation. Our previous phytochemical studies on E. multiradiatus resulted in the isolation of scutellarin, which is a known ‰avone glucuronide with comprehensive pharmacological actions. In present study, we investigated the inhibition action of scutellarin on high glucose-induced vascular in‰ammation in human endothelial cells (ECV304 cells). Consistent with previous reports, exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Up to 7 days of chronic incubation of human umbilical vein endothelial cells (HUVEC) with high glucose increased mRNA expression and production rate of MCP-1 in a time- and concentration (10-35 mM)-dependent manner, through upregulation of reactive oxygen species (ROS) generation and subsequent activation of p38 MAPK [106]. Consistent with previous reports, exposure of human endothelial ECV304 cells to high glucose for 24 h caused an increase of MCP-1 and intercellular adhesion molecule-1 (ICAM-1), and promoted cell adhesion between monocyte and ECV304 cells [107]. Furthermore, high glucose treatment on human acute monocytic leukemia THP-1 cells increased both mRNA and protein levels of MCP-1, enhanced the adhesion of THP-1 cells to endothelial cells, and the pathways reportedly involved oxidative stress, protein kinase C, ERK1/2, and p38 MAPK [108].…”
Section: Diabetic Complication - Cardiovascular Diseasesupporting
confidence: 80%
“…Up to 7 days of chronic incubation of human umbilical vein endothelial cells (HUVEC) with high glucose increased mRNA expression and production rate of MCP-1 in a time- and concentration (10-35 mM)-dependent manner, through upregulation of reactive oxygen species (ROS) generation and subsequent activation of p38 MAPK [106]. Consistent with previous reports, exposure of human endothelial ECV304 cells to high glucose for 24 h caused an increase of MCP-1 and intercellular adhesion molecule-1 (ICAM-1), and promoted cell adhesion between monocyte and ECV304 cells [107]. Furthermore, high glucose treatment on human acute monocytic leukemia THP-1 cells increased both mRNA and protein levels of MCP-1, enhanced the adhesion of THP-1 cells to endothelial cells, and the pathways reportedly involved oxidative stress, protein kinase C, ERK1/2, and p38 MAPK [108].…”
Section: Diabetic Complication - Cardiovascular Diseasesupporting
confidence: 80%
“…It has been shown that extract of Scutellaria barbata specifically targets tumor tissue. Recently, its anti-inflammatory and anti-tumor activities have been revealed (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…This causal relationship is currently being investigated. Moreover, others have suggested that Scu can protect against high glucose‐induced vascular inflammation, 29 which is also beneficial for the prevention of diabetic complications.…”
Section: Discussionmentioning
confidence: 99%